A cross-sectional study of medial longitudinal arch development in children with different BMI - Chen, Jing; Tang, Li; Yang, Xiaoxuan; Tang, Jing; Cheng, Qingfeng; Zhao, Chen; Zhang, Han (Frontiers in Pediatrics, 2024)
Introduction: The influence of excess weight on the development of children's feet remains a subject of debate. To further elucidate whether this relation occurs, this study compared arch morphology and flexibility in three groups of children with underweight, normal and overweight. Methods: 1532 children (807 boys, 725 girls), aged 7-11 years, participated in the study. The researchers measured the participants' height and weight, calculated their BMI, and categorised their weight status as underweight, normal weight or overweight. A three-dimensional foot model was taken by a three-dimensional plantar scanner under non-weight-bearing and weight-bearing conditions to obtain arch morphometric indices (arch index and arch volume) and arch flexibility index (arch volume index).Results: Analysis of the data showed that the arch index was higher in children with overweight compared to children with underweight and normal (p < 0.05), but the differences in arch volume and arch volume index in children with overweight compared to children with underweight and normal were not statistically significant (p > 0.05). All children were divided into flatfoot, normal and pes cavus group according to arch index, and the arch volume index was statistically significant (p < 0.01).Overweight was not absolutely associated with arch structure and arch flexibility in children from a three-dimensional perspective. Arch development is a long-term process, and it is not clear whether being overweight has an effect on soft tissue or bone formation. The future studies will focus on the effects of long-term overweight on foot structure and arch flexibility in children.